The Effect of Kahoot Media Use and Learning Motivation on Student Learning Outcomes in Mathematics Subjects - Shopia, Nur; Fatirul, Achmad Noor; Prayitno, Sunyoto Hadi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to determine the interaction between the use of kahoot media and learning motivation on student learning outcomes in mathematics subjects at SMA Al Islam Krian. With the implementation of this research, it is hoped that it can have several benefits, such as the potential to produce valuable insights and expand insights in academic courses. Especially related to the use of information technology is the understanding of how learning motivation and the application of Kahoot affect student learning outcomes in mathematics subjects. The research paradigm used in this study is a quantitative approach. The experimental research design used was Quasi Experimental Design - Nonequivalent Control Group Design. The control class was only given treatment using power point, while the experimental class received treatment in the form of free variables, namely Kahoot application media (X) and learning outcomes (Y) were bound variables or variables that were changed in this study. The value of mathematics learning outcomes is considered to be influenced by the element of student learning motivation. Therefore, the researcher included a moderate variable (M), namely the student’s motivation to learn. In this study, the research population is 431 students in class XI Special Class and Class XI Regular, then the research sample is students in class XI-4 (Special Class) as an experimental class totaling 36 students and class XI-10 (Regular Class) which is a control class of 36 students. The research instruments used were questionnaires and tests. Meanwhile, to analyze the data, the researcher used a 2-path annova analysis. Based on the results of the 2-path anova test, the significance value of interaction between learning media and learning motivation was 0.016 < 0.05 so that it can be interpreted that there is an interaction between kahoot learning media and student learning motivation on student learning outcomes